Histories : Ancient, Modern, Personal and Political - Brass, Tom, (Social Sciences E-Books Online, Collection 2026., 2026)
Histories examined here extend from the ancient to the modern, encompassing also the political and the personal. The reason for examining recent trends in the historiography of the Roman empire is because it is there, at the starting point of the historical trajectory on which the whole of Marxist theory is based, that attempts are being made to undermine its foundations. Against this the efficacy of class and much else besides is reasserted via an examination of how and why discourse about work, gender, and property relations features at the rural grassroots, together with a critical analysis of how and why discarding Marxism has contributed to the current empowerment of populism.